Kiat-Kiat Menumbuhkan Rasa Penerimaan Diri Resident Narkoba Dengan Bimbingan Konseling Melalui Metode TC - Maswandhani Destriando; Agus Suriadi (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
In general, there are still many drug addicts who do not know that what he is doing is wrong, because what he has done has harmed himself and others. Most residents have not accepted themselves, they are undergoing rehabilitation but not sincerely, they have not accepted their current situation. Therefore it is important to foster a sense of self-acceptance in drug addicts. Self-acceptance is a positive attitude towards oneself, being able and willing to accept oneself, both strengths and weaknesses, so that they can see a more positive future. Self-acceptance can be formed, self-acceptance can also be increased, so that they can accept the reality that is happening in their lives. through counseling guidance, self-acceptance can be grown in a drug addict. The TC (Therapeutic community) method is an effort for intrapersonal recovery of drug abusers to improve individual social functioning through individual strengthening carried out in rehabilitation centers by fostering a sense of self-acceptance and self-confidence, emotional management, behavioral pruning, self-discipline through a series of therapeutic activities and programs that are run, using the TC (Therapeutic Community) method, addicts can work together to foster a sense of self-acceptance because the TC concept, which is helping others, means the same thing. don't help yourself.